Low-Carbon Watershed Management: Potential of Greenhouse Gas Reductions from Wastewater Treatment in Rural Vietnam. (8th September 2016) - Nguyen, Lan Huong; Mohan, Geetha; Jian, Pu; Takemoto, Kazuhiko; Fukushi, Kensuke
Abstract : Currently in many cities and rural areas of Vietnam, wastewater is discharged to the environment without any treatment, which emits considerable amount of greenhouse gas (GHG), particularly methane. In this study, four GHG emission scenarios were examined, as well as the baseline scenario, in order to verify the potential of GHG reduction from domestic wastewater with adequate treatment facilities. The ArcGIS and ArcHydro tools were employed to visualize and analyze GHG emissions resulting from discharge of untreated wastewater, in rural areas of Vu Gia Thu Bon river basin, Vietnam. By applying the current IPCC guidelines for GHG emissions, we found that a reduction of GHG emissions can be achieved through treatment of domestic wastewater in the studied area. Compared with baseline scenario, a maximum 16% of total GHG emissions can be reduced, in which 30% of households existing latrines are substituted by Japanese Johkasou technology and other 20% of domestic wastewater is treated by conventional activated sludge.